Radiation doses to mediastinal organs at risk in early-stage unfavorable Hodgkin lymphoma– a risk stratified analysis of the GHSG HD17 trial - Oertel, Michael; Hering, Dominik; Baues, Christian; Kittel, Christopher; Fuchs, Michael; Kriz, Jan; Kröger, Kai; Vordermark, Dirk; Herfarth, Klaus; Engenhart-Cabillic, Rita; Lukas, Peter; Haverkamp, Uwe; et al. (Frontiers in Oncology, 2023)
Introduction The German Hodgkin Study Group (GHSG) HD 17 trial established the omission of radiotherapy (RT) for patients with early-unfavorable stage Hodgkin lymphoma being PET-negative after 2 cycles of BEACOPP escalated plus 2 cycles of ABVD. This patient group reveals heterogeneity in characteristics and disease extent which prompted us to perform a decisive dosimetric analysis according to the GHSG risk factors. This may help to tailor RT individually balancing risks and benefits. Methods For quality assurance, RT-plans were requested from the treating facilities (n= 141) and analyzed centrally. Dose-volume-histogram were scanned either paper-based or digitally to obtain doses to mediastinal organs. These were registered and compared according to GHSG risk factors. Results Overall, RT plans of 176 patients were requested, 139 of which had dosimetric information of target volume within the mediastinum. Most of these patients were stage II (92.8 %), had no B-symptoms (79.1 %) and were aged < 50 years (89.9 %). Risk factors were present in 8.6 % (extranodal involvement), 31.7 % (bulk), 46.0 % (elevated erythrocyte sedimentation rate) and 64.0 % (three involved areas), respectively. The presence of bulky disease significantly affected the mean RT doses to the heart (p=0.005) and to the left lung (median: 11.3 Gy vs. 9.9 Gy; p=0.042) as well as V5 of the right and left lung, respectively (median right lung: 67.4 % vs. 51.0 %; p=0.011; median left lung: 65.9 % vs. 54.2 %; p=0.008). Significant differences in the same organs at risk parameters could be found between the sub-cohorts with the presence or absence of extranodal involvement, respectively. In contrast, an elevated erythrocyte sedimentation rate did not affect dosimetry significantly. No association for any of the risk-factors and doses to the female breast was found. Conclusion: Pre-chemotherapy risk factors may help to predict potential RT exposure to normal organs and to critically review treatment indication. Individualized risk-benefit evaluations for patients with HL in early-unfavorable stage are mandatory.